Nutritional care in colorectal cancer—what is the state of play?. (25th October 2021) - Maunsell, Rose; Sodergren, Samantha; Hopkinson, Jane; Shaw, Clare; Foster, Claire; Wheelwright, Sally
Abstract: Aim: Nutrition is associated with aetiology and impacts outcomes in colorectal cancer (CRC). This study aimed to explore nutritional symptoms and concerns of patients with CRC and CRC dietetic resource across the UK. Methods: Study 1 is a descriptive analysis of nutrition‐related measures in the ColoRectal Wellbeing (CREW) study, a prospective 5‐year longitudinal cohort study of a representative sample of 872 adults with non‐metastatic CRC. Study 2 is a descriptive analysis of data collected using a freedom of information request to all UK trusts/boards on dietetic resources for CRC. Results: Study 1 found that 31% of CREW participants wanted more diet and lifestyle advice. At 3 months post‐surgery, 10% reported poor appetite. A fifth experienced weight loss and 16% had concerns regarding weight loss 9 months post‐surgery. In study 2 just 3% of hospitals providing CRC services had a dedicated CRC dietitian (hepato‐pancreato‐biliary, 11.1%; head and neck cancer, 14.3%). There was no dietetic outpatient follow‐up of CRC patients in 72% of hospitals. Conclusions: Dietetic resource for patients with CRC is scarce even though weight loss, poor appetite and unmet needs are common and persist over time. Work is needed to embed nutritional care into the management of patients with CRC.